Where are the children now? [large type] - Clark, Mary Higgins; Burke, Alafair (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"More than four decades since readers first met Nancy Harmon and her children, comes the thrilling sequel to the groundbreaking book that set the stage for future generations of psychological suspense novels. A lawyer turned successful podcaster, Melissa has recently married a man whose first wife died tragically, leaving him and their young daughter, Riley, behind. While Melissa and her brother, Mike, help their mom, Nancy, relocate from Cape Cod to the Hamptons, Melissa's new stepdaughter goes missing. Drawing on the experience of their own abduction, Melissa and Mike race to find Riley to save her from the trauma they still struggle with--or worse"--